(untitled) (Stavební obzor - Civil Engineering Journal, 2019)
Shuttle steel shelves (steel shelves equipped with shuttles) are popular in modern logistics. The safety of shuttle steel shelves is an issue due to the complicated dynamic load that develops when the shuttles are in operation. As deformation is an important index of structural safety, this study uses a DPS (digital photography system) based on the PST-IM-MP (photograph scale transformation-image matching-motion parallax) method to monitor shuttle steel shelves: a digital camera (SONY350) was used to monitor the dynamic deformation of shuttle steel shelves when the shuttles began to move, accelerated, moved at constant speed, decelerated and stopped. Then, the deformation trends of the shuttle steel shelves were depicted to study the moving trajectory in a local area. Moreover, we analysed the stresses in the shuttle steel shelves based on these monitoring data. The results showed that the PST-IM-MP method can meet the accuracy requirements in monitoring the dynamic deformation of steel shelves as the maximum and minimum measurement errors were 0.74 pixels and 0.34 pixels in the comprehensive direction, respectively. The shuttle steel shelves were robust because the deformations were elastic and within the allowed10mm. Shear and tension stresses developed in the shuttle steel shelves when the shuttles were in operation. Thus, in the future DPS will become popular for monitoring shuttle steel shelves in real time to warn of possible dangers and mitigate hazards. Additionally, the monitoring data can be used to study the stability of the shuttle steel shelves to improve the related stability design theory.